Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type. (16th July 2021) - Duong, Tra‐My N.; Le, Thanh‐Van; Tran, Khanh‐Linh H.; Nguyen, Phuong‐Tuyen; Nguyen, Bich‐Phuong T.; Nguyen, Thu‐Anh; Nguyen, Huong‐Lan P.; Nguyen, Bich‐Ngoc T.; Fisher, Matthew C.; Rhodes, Johanna; Marks, Guy; Fox, Greg J.; et al.
Summary: Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR34 /L98H most frequent (34/38).